2021
DOI: 10.15244/pjoes/131979
|View full text |Cite
|
Sign up to set email alerts
|

Inoculation of Pinus halepensis with the Ectomycorrhizal Fungi Scleroderma Helps in Phytoremediation of Soil Polymetallic Pollution

Abstract: This study aims to evaluate the effectiveness of Pinus halepensis inoculated with the ectomycorrhizal fungi spores belonging to Scleroderma in phytoremediation of polymetallic soil. Tailings were collected in the Kettara polymetallic abandoned mine in southern Morocco and diluted with sand in the following proportions, 10%, 25%, 50% and 75%. The pots experiment was conducted for six months under greenhouse conditions. The results show that the studied plant reveals a great tolerance even at high proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, the presence of Pb in soil may interfere with the symbiosis establishment, hindering the plant-fungus recognition or slowing down the root colonization. The negative effect of Pb and other heavy metals on the abundance of ectomycorrhizas was already demonstrated by different authors (Bojarczuk & Kieliszewska-Rokicka, 2010;Chappelka et al, 1991;Ouatiki et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…However, the presence of Pb in soil may interfere with the symbiosis establishment, hindering the plant-fungus recognition or slowing down the root colonization. The negative effect of Pb and other heavy metals on the abundance of ectomycorrhizas was already demonstrated by different authors (Bojarczuk & Kieliszewska-Rokicka, 2010;Chappelka et al, 1991;Ouatiki et al, 2021).…”
Section: Discussionmentioning
confidence: 70%
“…Zn, Cd, Pb) in P. halepenisi seedlings when grown under greenhouse conditions in a mixture of polymetallic mine tailings and sand (Ouatiki et al 2022). In a related study, (Ouatiki et al 2021) reported that Scleroderma-containing inoculants also resulted in an increase in the biomass of inoculated P. halepensis seedlings.…”
Section: Discussionmentioning
confidence: 96%
“…For example, a greenhouse study by Cumming and Weinstein (1990) indicated that the aluminum tolerance of the Pitch pine can be influenced by its symbiotic association with the ectomycorrhizal fungus Pisolithus tinctorus . Greenhouse studies have also shown that certain ECMF species can ameliorate the toxic effects of zinc (Adriaensen et al 2006) and cadmium on Pinus sylvestris (Krznaric et al 2009) and P. halepensis (Ouatiki et al 2021; Ouatiki et al 2022). Field studies of pre‐inoculated Jack pine ( P. banksiana ) seedlings have shown that the persistence of ECMF species can be influenced by multiple factors, including the physicochemical characteristics of the soils in which they reside (McAfee & Fortin 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Phytoremediation innovations are available for various environments and types of contaminants [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. However, the innovation of the present paper was the screening of native plant species for their potential and suitability for remediation of the study area.…”
Section: Introductionmentioning
confidence: 99%